Search for long-lived, multi-charged particles in pp collisions at s√=7 TeV using the ATLAS detector - Aad, G. (2013)
A search for highly ionising, penetrating particles with electric charges from |q| = 2e to 6e is performed using the ATLAS detector at the CERN Large Hadron Collider. Proton–proton collision data taken at √s = 7 TeV during the 2011 running period, corresponding to an integrated luminosity of 4.4 fb−1, are analysed. No signal candidates are observed, and 95% confidence level cross-section upper limits are interpreted as mass-exclusion lower limits for a simplified Drell–Yan production model. In this model, masses are excluded from 50 GeV up to 430, 480, 490, 470 and 420 GeV for charges 2e, 3e, 4e, 5e and 6e, respectively